Local Expression of MMP-7 in Oral Cancer - Habib, Manal A.; Abdul-Majeed, Ban A.; Al-sened, Maha M. (AL-Kindy College Medical Journal, 2011)
Background: Squamous cell carcinoma of the oral cavity (OSCC) is a highly invasive neoplasm. Many MMPs play role in human cancer invasion and metastases. Aim: Estimating The MMp-7 expression level in HPV-16 positive and HPV-16 negative OSCC paraffin embedded sections. Method: Biopsies from thirty three patients with oral squamous cell carcinoma (OSCC) were obtained and investigated for the presence of HPV-16 RNA with the application of ISH and the MMP-7 expression level using IHC . Results: Expression level of MMP-7 found to be high in OSCC sections 29 (87.8%) cases with no significant difference in its expression level between HPV-16 positive and HPV-16 negative OSCC cases p= 1.00. Conclusion: MMp-7 found to be expressed in high level in OSCC with no significant relevance to HPV- 16.